Cellular infiltrate of the jejunum after re-introduction of dietary gluten in children with treated coeliac disease. Issue 7 (July 1976) - Lancaster-Smith, M; Packer, S; Kumar, P J; Harries, J T
Abstract : Jejunal lamina propria plasma cells and eosinophils and intraepithelial lymphocytes were raised in coeliac children on gluten-containing diets, but only intraepithelial lymphocytes were increased in patients on gluten-free diets. In contrast, lamina propria lymphocytes were reduced in children with coeliad disease on gluten-containing diets but were normal in paitents on gluten-free diets. In children with coeliac disease who were studied serially, lamina propria plasma cells and eosinophils and intraepithelial lymphocytes increased, and lamina propria lymphocytes decreased, within three months of the reintroduction of gluten to the diet. These observations are essentially similar to those made in the adult form of the disease and suggest that more than one type of immunological reaction is involved in the pathogenesis of the jejunal lesion.